2020
DOI: 10.3389/fmolb.2020.00088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alternative Allosteric Sites in Glycolytic Enzymes for Potential Use as Species-Specific Drug Targets

Abstract: Three allosteric glycolytic enzymes, phosphofructokinase, glyceraldehyde-3 phosphate dehydrogenase and pyruvate kinase, associated with bacterial, parasitic and human species, were explored to identify potential allosteric sites that would be used as prime targets for species-specific drug design purposes using a newly developed approach which incorporates solvent mapping, elastic network modeling, sequence and structural alignments. The majority of binding sites detected by solvent mapping overlapped with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…The model allows one to observe the causality and to quantify the energetics of allosteric communication upon ligand binding and/or mutations in a protein, to identify potential regulatory exosites through a reverse perturbation of allosteric communication, and to obtain a comprehensive picture, allosteric signaling map (ASM), of per-residue allosteric signaling in proteins. The SBSMMA was thoroughly benchmarked in our previous works, , and it was successfully used in experimental , and theoretical projects as a predictive and analytical tool. These works describe allosteric effects of mutations, ,, regulation of protein–protein interactions, prediction of druggable sites, and effects of the ligand binding, to name a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model allows one to observe the causality and to quantify the energetics of allosteric communication upon ligand binding and/or mutations in a protein, to identify potential regulatory exosites through a reverse perturbation of allosteric communication, and to obtain a comprehensive picture, allosteric signaling map (ASM), of per-residue allosteric signaling in proteins. The SBSMMA was thoroughly benchmarked in our previous works, , and it was successfully used in experimental , and theoretical projects as a predictive and analytical tool. These works describe allosteric effects of mutations, ,, regulation of protein–protein interactions, prediction of druggable sites, and effects of the ligand binding, to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…The SBSMMA was thoroughly benchmarked in our previous works, , and it was successfully used in experimental , and theoretical projects as a predictive and analytical tool. These works describe allosteric effects of mutations, ,, regulation of protein–protein interactions, prediction of druggable sites, and effects of the ligand binding, to name a few. The SBSMMA is implemented in web resources, the server AlloSigMA , and database AlloMAPS, which are proven to be instrumental in elucidation of allosteric mechanisms and actions of allosteric effectors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, APOP can also detect alternative allosteric pockets as high-ranked pockets, indicating its potential utility for designing ways to alter protein activity by targeting newly identified ligand-binding pockets. Prediction of alternate allosteric pockets can facilitate the effective drug targeting of enzymes such as Phosphofructokinase, Glyceraldehyde-3 phosphate dehydrogenase, and Pyruvate kinase ( Ayyildiz et al 2020 ). APOP can also predict the known allosteric ligand-binding pockets as the top-ranked pockets in different protein conformational states.…”
Section: Discussionmentioning
confidence: 99%
“…They found that functional sites possess increased communication propensities and secondary structures are quite efficient in mediating allosteric communications. Recently, Ayyildiz et al incorporated elastic network modeling with solvent mapping and sequential and structural alignments to identify species-specific allosteric sites in glycolytic enzymes of bacteria, parasites, and humans. Ota et al used anisotropic thermal diffusion, a nonequilibrium MD simulation method, , to study the intramolecular signaling pathways in PDZ domain proteins.…”
Section: Identification Of Allosteric Sites and Pathways In Proteinsmentioning
confidence: 99%